PERANAN CIVIC COMMUNITY DALAM MENDORONG PEMUDA SEBAGAI PELOPOR KEMANDIRIAN BANGSA (Studi kasus pada komunitas “Pasukan Kresek” di Kabupaten Malang Jawa Timur) - Mawarti, Rista Ayu; Sundawa, Dadang (Universitas Islam Negeri Raden Fatah Palembang, 2016)
The role of civic community in encouraging the youth as the pioneer of the nation self- reliance. This study aims to explore the role of civic community in optimising the potential of youth in order to become the pioneer of nation self-reliance. The research method used, i.e. qualitative approach to the design of case studies on community